The relationship between soluble lymphocyte activation gene-3 and coronary artery disease - Xiong, Xinlin; Duan, Zonggang; Zhou, Haiyan; Niu, Li; Luo, Zhenhua; Li, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Soluble lymphocyte activation gene 3 (sLAG3) may be used for diagnosis or prognosis in various diseases. However, the relationship between sLAG3 and CAD are still unclear. This study aimed to investigate the levels of sLAG3 in patients with CAD, and its potential clinical association with the disease. Methods: A total of 66 subjects (49 patients with CAD and 17 control subjects without CAD) were enrolled. The sLAG3 level was measured using enzyme-linked immunosorbent assay (ELISA) kits. Clinical variables included demographics, biochemical markers, coronary angiography status, and ejection fraction of the heart (EF) were collected, and Gensini scores were calculated. LAG3 gene data was extracted from three datasets (GSE23561, GSE61144, GSE60993) in Gene Expression Omnibus (GEO) to compare differential expression between CAD and control subjects. Results: The sLAG3 level was significantly lower in the CAD vs the controls (P<0.05), and negatively associated with CAD [odds ratio (OR): 0.212, 95% confidential interval (CI): 0.060-0.746, P<0.05]. Furthermore, the area under the curve (AUC) of sLAG3 level was significant (P<0.05). The sLAG3 level in subjects with body mass index (BMI) ≥24 kg/m2 was lower compared to those with BMI <24 kg/m2 (P<0.05). The sLAG3 level was also negatively associated with BMI and diabetes mellitus (P<0.05), though not associated with the Gensini scores or EF (P>0.05). Lastly, the LAG3 gene expression in peripheral whole blood of patients with CAD were down-regulated compared to healthy controls (P<0.05). Conclusions: The sLAG3 level was negatively associated with the occurrence but not severity of CAD. Meanwhile, the sLAG3 was negatively associated with BMI and diabetes mellitus, suggesting the reduced sLAG3 might be a novel risk factor for developing CAD.